A review of filamentous sludge bulking controls from conventional methods to emerging quorum quenching strategies. (1st June 2023) - Lu, Xin; Yan, Ge; Fu, Liang; Cui, Bin; Wang, Jinfeng; Zhou, Dandan
Highlights: Classical bulking hypotheses limit the application of conventional bulking control. The microbial interactions are regulated through quorum sensing behaviors. Functional signal molecules regulate specifically filamentous microorganisms. Filamentous bulking has been verified to be related with quorum sensing. Quorum quenching is effective and precise to inhibit filamentous bulking. Abstract: Filamentous bulking, which results from the overgrowth of filamentous microorganisms, is a common issue that frequently disrupts the stable operation of activated sludge processes. Recent literature has paid attention to the relationship between quorum sensing (QS) and filamentous bulking highlighting that the morphological transformations of filamentous microbes are regulated by functional signal molecules in the bulking sludge system. In response to this, a novel quorum quenching (QQ) technology has been developed to control sludge bulking effectively and precisely by disturbing QS-mediated filamentation behaviors. This paper presents a critical review on the limitations of classical bulking hypotheses and traditional control methods, and provides an overview of recent QS/QQ studies that aim to elucidate and control filamentous bulking, including the characterization of molecule structures, the elaboration of QS pathways, and the precise design of QQ molecules to mitigate filamentous bulking. Finally, suggestions for further research and development of QQ strategies for precise bulking control are put forward. Graphical abstract: Image, graphical abstract